2015
DOI: 10.1186/s12957-015-0621-7
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic importance of the number of metastases in pulmonary metastasectomy of colorectal cancer

Abstract: BackgroundThe presence of multiple metastatic pulmonary nodules is a predictor of poor survival after pulmonary metastasectomy. However, there is a paucity of data addressing the exact number of pulmonary metastases over which prognosis becomes grave. The aim of our study is to investigate the prognosis of pulmonary metastasectomy from colorectal cancer (CRC) depending on the number of pulmonary metastases.MethodsPatients who had undergone pulmonary metastasectomy for CRC between November 1994 and December 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 25 publications
2
34
0
2
Order By: Relevance
“…Equally, patients with pulmonary metastasis may benefit from surgical resection [55,56,57]. However, patient selection plays a crucial role with regard to prognosis.…”
Section: Treatment Strategies In Advanced Stages Of Colorectal Cancermentioning
confidence: 99%
“…Equally, patients with pulmonary metastasis may benefit from surgical resection [55,56,57]. However, patient selection plays a crucial role with regard to prognosis.…”
Section: Treatment Strategies In Advanced Stages Of Colorectal Cancermentioning
confidence: 99%
“…In the reports by Gonzalez and Embun, a short DFI was prognostic of decreased survival-rate (10,11). However, in several other studies, DFI did not reach statistical significance (8,9,22). It seems reasonable to speculate that a short DFI would reflect a more aggressive disease or a more advanced primary tumor, which in turn would be detrimental to survival.…”
Section: Discussionmentioning
confidence: 93%
“…Although the clinical factors analyzed in each study were different, the roles of some predictors had been confirmed in many studies [9][10][11][12], including: the distribution and size of lung metastases, the status of pulmonary lymph nodes, the CEA level of lung lesions before surgery, and the existence of liver metastases, etc. [10,11,[13][14][15][16][17]. Tomohiko et al retrospectively investigated 1030 patients who underwent resection of colorectal cancer with lung metastasis, they found that more than one lung metastases, maximum tumor diameter of 2 cm or more suggested that patients with CRC-PM a poor prognosis [18].…”
Section: Discussionmentioning
confidence: 99%
“…However, heterogeneity of tumor sizes in multiple CRC-PM was an independent factor of the prognosis of the patients [19]. The association of survival and other factors, like age, gender, ASA score, primary tumor staging, tumor-free interval was controversial in different studies [14,[20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%